Regional disparities in Ghana: Policy options and public investment implications - Al-Hassan, Ramatu M.; Diao, Xinshen (International Food Policy Research Institute, 2007)
This paper sets out to identify avenues for pro-poor growth in Ghana, focussing on agricultural opportunities, particularly in northern Ghana. Using an economywide, multimarket model and based on time series production data between 1991 and 2000 and Ghana Living Standards Survey data of 1991/92 and 1998/99, this paper analyzes the possible poverty reduction trends up to 2015 by assuming different patterns of growth. The results show that agriculture-led growth has a larger poverty reducing effect than nonagriculture-led growth.